2015
DOI: 10.1016/j.eurpsy.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Fish consumption and depressive symptoms in undergraduate students: A cross-sectional analysis

Abstract: Frequent fish consumption in undergraduate students seems to moderate depressive symptoms. Further research is warranted to clarify the causality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…This tendency was lost in the multivariate model or a model including covariates of dietary intake of vitamin D, UV exposure frequency, and living with children. Therefore it is suggested that this was the consequence of confounding effects of less exposure to sunlight and lower dietary consumption of vitamin D among younger populations in Japan[9,30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This tendency was lost in the multivariate model or a model including covariates of dietary intake of vitamin D, UV exposure frequency, and living with children. Therefore it is suggested that this was the consequence of confounding effects of less exposure to sunlight and lower dietary consumption of vitamin D among younger populations in Japan[9,30].…”
Section: Resultsmentioning
confidence: 99%
“…In Japan, because fish is a primary component of the traditional diet, the risk of vitamin D deficiency is rarely discussed. However, studies indicate that younger people consume less fish [912], and while females appear to be at higher risk of vitamin D deficiency because they tend to avoid direct sunlight exposure to prevent skin-tanning, may be malnourished from maintaining a lean proportion [13]. The importance of monitoring the vitamin D status in Japan has only recently been demonstrated [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to prospective studies, many cross‐sectional studies examined the association between fish consumption or omega‐3 fatty acid intake and depression (Albanese et al, ; Barberger‐Gateau et al, ; Beydoun et al, ; Bountziouka et al, ; Chrysohoou et al, ; Daley, Patterson, Sibbritt, & MacDonald‐Wicks, ; Hamazaki et al, ; Hoffmire, Block, Thevenet‐Morrison, & van Wijngaarden, ; Jacka et al, ; Kamphuis et al, ; Kesse‐Guyot et al, ; Mihrshahi et al, ; Murakami et al, ; Suominen‐Taipale et al, ; Supartini, Oishi, & Yagi, ; Tanskanen et al, ; Timonen et al, ; Wu et al, ; Yang & Je, ). Most of the studies reported significant inverse associations between fish consumption and depression (Barberger‐Gateau et al, ; Bountziouka et al, ; Chrysohoou et al, ; Hamazaki et al, ; Supartini et al, ; Suominen‐Taipale et al, ; Tanskanen et al, ; Timonen et al, ; Wu et al, ), and some of the studies showed strong inverse associations, suggesting more than 50% decreased prevalence of depression for people with high fish consumption (Albanese et al, ; Chrysohoou et al, ; Suominen‐Taipale et al, ; Supartini et al, ; Timonen et al, ). Studies evaluating omega‐3 fatty acid intake and depression also mostly found significant or nonsignificant inverse associations between omega‐3 fatty acid intake and the prevalence of depression (Beydoun et al, ; Hoffmire et al, ; Kamphuis et al, ; Kesse‐Guyot et al, ; Murakami et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The criterion validity of the CES-D scale has been well established in Western ( 48 ) and Japanese ( 47 ) subjects. Because of a previously demonstrated over-rating of symptoms by the Japanese ( 49 , 50 ) , particularly younger people ( 51 , 52 ) , prevalent cases of depressive symptoms were defined as having a CES-D score of ≥23 ( 49 ) for young women and ≥19 ( 49 ) for middle-aged women, rather than a widely used cutoff point of ≥16 ( 47 , 48 ) . The use of the cutoff points ≥16 for both age groups, ≥19 for young women and ≥23 for middle-aged women did not change the conclusion on the association between the diet quality score and depressive symptoms (data not shown).…”
Section: Methodsmentioning
confidence: 99%